(untitled) (Journal of Parents and Teachers, 2014)
This article basically answers two main questions: first, why an international year of astronomy? Because of the valuable contribution of astronomy to science and our society. This celebration coincides with the invention of the telescope in 1609 by Galileo and the publication of Astronomia nova by Kepler. Second, why is important that schools spread this science? In order to support, improve and promote the study of science because of its social and cultural importance.